Gestão de projeto educacional: concepção e aplicação em uma Unidade Básica de Saúde - Salomon, Eliana de Fátima Souza (2018)
Although implemented in Brazil, the Family Health Strategy policy, as a tactic to construct a new service model based on the perspective of the law and concepts such as integrality and relation between sectors, the correlation between the standards of management, in which traditional methods prevail, anchored in rigid, hierarchical, vertical structures and with centralized decision processes can be observed. On the other hand, it is possible to observe others whom seek to exercise in their management an expanded concept of health, through the multiple factors that interfere in the health / disease process, recognizing institutional mechanisms and practices that guarantee the means for their effectiveness. This reflection brought up the objective of investigating concepts and principles currently developed about Project Management by the administration sciences, seeking to organize a set of suggestions that could improve the conduction of the programs developed in a Basic Health Unit - Family Health Strategy. The chosen locus was a unit from a city in the interior of Minas Gerais, with problems to achieve its objectives. For that, the methodological approach was the qualitative approach under a involved observation procedure, considering that the intervention can be made feasible through the diagnosis of reality, building action strategies and organizing the collective for a management restructuring. The intention was to collaborate with the program in the educational actions management, the Management of Educational Projects. The studies were profound on the main theories of administrative management subjects, highlighting and organizing characteristics and procedures that, when incorporated into project management collaborated to guide and improve their results. These were based on the knowledge areas of PMBOK (2014), understood as appropriated, and allied to those based on pedagogical elements, especially based on masters as Masetto (2010), Cifuentes (2014) and Paro (2015). As a result, a Permanent Education Program was implemented for the employees of the multidisciplinary teams in the Family Health Strategy, in which two objectives were achieved: a problem was addressed which made it difficult to manage the other projects more effectively, through the training of the team involved, and the Program was built applying the theoretical concepts of Project Management, integrating Education and Administration Sciences contemplated in this thesis. With the change, it was verified the transformation of the attitudes and actions of the employees in their functions. Is expected from the study to contribute to the understanding of a successful Educational Project Management practice